Sistem Pendukung Keputusan Perpanjangan Kontrak Kerja Karyawan PT.Nexwave Jakarta Menggunakan Metode SAW - Desy Purnamasari Rahmawati; Tonton Taufik Rachman (Jurnal Dimamu, 2023)
The extension of the employee's employment contract is one of the important aspects that affect the performance and motivation of employees to do better at work. The problem of extending the employment contract of employees at PT. NexWave, namely the assessment is still done manually, there are no standard criteria in determining employees who are entitled to have their work contracts extended, and the decision-making process is not based on a solid basis. The method using Simple Additive Weighting (SAW) method and was built with the Unified Modeling Language (UML) as the system design. The programming language used is the PHP framework codeigniter and database using MySql. The test used is Black Box Testing. This research produces a decision support system that can be used in an easy, structured, and computerized manner by setting standard criteria, and a special method, namely the SAW method. The result of the decision is clearer because it can be separated based on the results of the assessment, namely the value of ?0,7 the employee's employment contract can be extended, while <0,7 the employee's employment contract cannot be extended.